My first book of haiku poems a picture, a poem and a dream : classic poems by Japanese haiku masters - Ramirez-Christensen, Esperanza U. 1946- (Tuttle Publishing, 2019)
20 classic poems by Issa, Shiki, Basho, and other great Japanese haiku masters presented in English, Japanese characters, and Romaji with interpretations
Text englisch und japanisch
Keywords: Haiku / Translations into English / Juvenile literature; Haiku; Japanese language materials / Bilingual; Juvenile works; Translations; Picture books; Bilderbuch; Anthologie; Kinderbuch